IMPLEMENTATION OF AI CHATBOTS AND ROBO-ADVISORS IN BANKING: TRANSFORMATION OF CUSTOMER BEHAVIOR AND SERVICE QUALITY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines how the implementation of artificial intelligence technologies, specifically AI chatbots and robo-advisors, in the banking sector of the Republic of Uzbekistan has transformed customer behavior and service quality. The topic is highly relevant in the context of the modern digital economy, as rapid advancements in artificial intelligence technologies have led banks to gradually adopt AI chatbots and robo-advisors in recent years. The main objective of the study is to identify the impact of AI technologies on the operational efficiency of the banking system, customer trust, and service quality indicators. The research utilizes data obtained from the Central Bank of the Republic of Uzbekistan, the Statistics Agency, and the research division of the international consulting company McKinsey & Company. The article also analyzes the role of the “Digital Uzbekistan – 2030” Strategy, the Law “On Banks and Banking Activities,” and presidential decrees in promoting the digital transformation of the banking sector. The methodology is based on a “before-and-after” analysis approach and comparative international analysis methods.The findings indicate that, according to the Central Bank of the Republic of Uzbekistan’s Digital Banking Services Statistical Reports [1], the average service time in eight commercial banks that implemented AI chatbots decreased from 4.8 minutes to 2.1 minutes during the period 2022–2024.
Keywords: Artificial intelligence, chatbot, robot consultant, banking system, client behavior, digital transformation, quality of service, banks of Uzbekistan.